2023
DOI: 10.1002/eco.2573
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in leaf traits in response to experimental precipitation increase: Wettability, foliar water uptake and gas exchange

Abstract: Water availability is one of the factors affecting plant growth and development, especially in arid and semiarid environments. Changes in precipitation due climate change alter water availability to plants impacting on plant physiology. Numerous studies have focused on plant response to reduced precipitation and less on the effects of increased precipitation. The main objective of this study was to evaluate biophysical and physiological leaf traits in response to experimental water addition in four dominant sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…Our results indicate a low plasticity of Patagonian steppe species to water addition. Although in a recent study in the same area, Cavallaro et al (2023) observed that these species are relatively plastic to water addition, the magnitude of plasticity was higher in functional traits than in morphological traits. Increased leaf carbon assimilation under the +W treatment observed by Cavallaro et al (2023) was not reflected in higher productivity in the present study.…”
Section: Response Of Plant Species To Water and Nitrogen Addition: Pl...mentioning
confidence: 68%
See 2 more Smart Citations
“…Our results indicate a low plasticity of Patagonian steppe species to water addition. Although in a recent study in the same area, Cavallaro et al (2023) observed that these species are relatively plastic to water addition, the magnitude of plasticity was higher in functional traits than in morphological traits. Increased leaf carbon assimilation under the +W treatment observed by Cavallaro et al (2023) was not reflected in higher productivity in the present study.…”
Section: Response Of Plant Species To Water and Nitrogen Addition: Pl...mentioning
confidence: 68%
“…Although in a recent study in the same area, Cavallaro et al (2023) observed that these species are relatively plastic to water addition, the magnitude of plasticity was higher in functional traits than in morphological traits. Increased leaf carbon assimilation under the +W treatment observed by Cavallaro et al (2023) was not reflected in higher productivity in the present study. Photoassimilates were probably allocated to roots or other functions (e.g., anti-herbivory defences) rather than to increase ANPP.…”
Section: Response Of Plant Species To Water and Nitrogen Addition: Pl...mentioning
confidence: 68%
See 1 more Smart Citation
“…Soil resistance of plant leaves refers to the resistance of plants to adverse factors in the soil, which is a comprehensive ability, including drought resistance, cold resistance, salinity resistance and other abilities. Changes in the wettability of plant leaves affect the exchange of air and water between the plant and the outside world, thereby affecting photosynthesis and respiration (Shi et al, 2011;Holder, 2012;Cavallaro et al, 2023). Wettability of the leaf surface can effectively improve water distribution within the plant (Gotsch et al, 2014;Ali et al, 2022), and also inhibit the exchange of Frontiers in Materials frontiersin.org gases at the interface, which promotes the growth of pathogens (Sase et al, 2008).…”
Section: Discussionmentioning
confidence: 99%